Tête-à-tête avec la charge mentale | Le Devoir - Saint-Jacques, Sylvie (Le Devoir, 2019)
La fameuse « charge mentale », qui se définit vaguement comme la somme des tâches non rémunérées qui alourdissent le quotidien et la matière grise des femmes, fait l’objet d’un nombre exponentiel d’ouvrages populaires et universitaires ces dernières années. Dans la foulée de Fallait demander de la bédéiste Emma et d’autres variations sur le même thème, Si nous sommes égaux, je suis la fée des dents est le fruit du travail de recherche pratique et de réflexions de la travailleuse sociale Amélie Châteauneuf, qui a voulu concevoir un outil pour les couples avec ou sans enfant.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; charge mentale; conciliation famille-travail; division sexuelle du travail; famille; maternité; projet charge mentale; périodes historiques; québec; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; thématiques; travail

Paid–unpaid work continuum of women: Home-based workers and self-employed women in the national capital region - Sengupta, Sudeshna (Indian Journal of Labour Economics, 2019)
Women’s work is a continuum that intersperses productive work with reproductive work, unpaid work with paid work and all kinds of activities with leisure and self-care. She plans, manages and implements her work at home, often being responsible for all the three domains. Women from working-class families may seem to be making a “choice” in deciding the continuum, and delving deep, we find that it is more often a “coping mechanism” in “managing poverty” of all forms—income, time and opportunity. This paper explores how women’s organisation of work is influenced by the interplay of three institutions—State, market and family, and how gendered division of work is reproduced in the process. © 2019, Indian Society of Labour Economics.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; division sexuelle du travail; famille; inde; pauvreté; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; thématiques; travail; travail de reproduction; travail gratuit; travail rémunéré; travailleuses à domicile

La sous-valorisation de l’expertise des femmes dans les médias, des chiffres et un projet - Shine, Laura; Sondarjee, Maïka (Revue L'Esprit libre, 2019)
Un panel politique dans une émission télévisée du matin. Un article dans une revue grand public. Une table ronde à la radio. Qu’ont en commun ces trois scénarios médiatiques? Les femmes y sont toujours minoritaires, voire absentes. En fait, les femmes représentent en moyenne 29 % des voix entendues comme expertes dans les grands médias canadiens1.
Keywords: 2000 à aujourd'hui; amériques; approches et analyses; canada; discours dominant; domination masculine; environnement; femmes expertes; inégalités; médias; projet charge mentale; périodes historiques; rapports sociaux de sexe; régions géographiques; syndrôme de l'imposteur; systèmes d'oppressions; thématiques; travail

Delivered by women, led by men: A gender and equity analysis of the global health and social workforce - World Health Organization (World Health Organization, 2019)
Demographic changes and rising health care demands are projected to drive the creation of 40 million new jobs by 2030 in the global health and social sector. In parallel, there is an estimated shortfall of 18 million health workers, primarily in low- and middle-income countries, required to achieve the Sustainable Development Goals (SDGs) and universal health coverage. The global mismatch between health worker supply and demand is both a cause for concern and a potential opportunity. Since women account for 70% of the health and social care workforce, gaps in health worker supply will not be closed without addressing the gender dynamics of the health and social workforce. The female health and social care workers who deliver the majority of care in all settings face barriers at work not faced by their male colleagues. This not only undermines their own well-being and livelihoods, it also constrains progress on gender equality and negatively impacts health systems and the delivery of quality care. In November 2017, the World Health Organization (WHO) established the Gender Equity Hub (GEH), co-chaired by WHO and Women in Global Health under the umbrella of the Global Health Workforce Network. The GEH brings together key stakeholders to strengthen gender-transformative policy guidance and implementation capacity for overcoming gender biases and inequalities in the global health and social workforce, in support of the implementation of the Global Strategy on Human Resources for Health: Workforce 2030, and the Working for Health five-year action plan (2017–2021) of WHO, the International Labour Organization (ILO) and the Organisation for Economic Co-operation and Development (OECD). In 2018, the GEH identified and reviewed over 170 studies in a literature review of gender and equity in the global health workforce, with a focus on four themes: occupational segregation; decent work free from bias, discrimination and harassment, including sexual harassment; gender pay gap; and gender parity in leadership. This report will inform the next phase of the work of the Global Health Workforce Network GEH, which seeks to use these research findings to advocate gender-transformative policy and action.
https://apps.who.int/iris/handle/10665/311322
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; discours dominant; droits des femmes*; inégalités; inégalités salariales; projet charge mentale; périodes historiques; rapports sociaux de sexe; systèmes d'oppressions; thématiques; travail; travailleureuses de la santé